VIRAL INFECTIONS THAT THREATEN FISH FARMING IN INDONESIA - Yahya, Andi Muhammad; Makkarumpa, Andi Nurul Atiqa Faizah; Ngopo, Frinth Azarya Kuriakos; Maulyda, Ishika; Thamrin, Muhammad Fathiyakan; Zahrani, Putri Dyah; Putri, Vinka Melani; Apada, Andi Magfira Satya; Rell, Fedri (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p20, 2023)
Indonesia as a maritime country that has fish resources that cannot be separated from various types of virus infections. Viral infections in fish cause death due to multiorgan damage to fish such as necrosis and hemorrhage. Fish deaths result in economic losses for fish farmers. The lack of knowledge of fish farmers about fish diseases and their prevention is one of the factors in the high cases of viral infectious diseases in fish. This paper is to present fish diseases due to viral infections that threaten fish farming in Indonesia such as: Viral Nervous Necrosis, Koi Herpes Virus, Channel Catfish Virus Diseases, Infectious Pancreatic Necrosis, and Lymphocystic Disease Virus. The source of the study in this paper comes from research reports or literature on viral infections in fish, specifically case reports on fish farming in Indonesia. The viral infectious disease can be acute or chronic where the infection occurs due to the presence of virus-carrying fish so that it spreads and infects other fish. It is hoped that this paper will be a source of information on viral diseases in fish that can help in the prevention and control of viruses in fish. Improving water quality, securing water temperature, and selecting the right seeds will be the first actions in handling and preventing viral infectious diseases in fish. In addition, socialization from relevant agencies is needed to provide guidance to fish farmers in especially in disease prevention